School counselors’ leadership skills in aceh province, indonesia: a survey of conceptual, technical, and interpersonal skills - Abu Bakar; Fajriani Fajriani; Yulizar Yulizar (Jurnal Konseling dan Pendidikan, 2026)
This study explores the leadership skills profile of school counselors in Aceh, Indonesia, in light of rising expectations for counselors to serve not only as service providers but also as leaders in coordinating comprehensive student support systems within schools. Despite increasing focus on counselor leadership, there is limited empirical data on how leadership skill dimensions are distributed among school counselors in local educational contexts. Based on Northouse’s leadership skills framework which views leadership through conceptual, technical, and interpersonal skills this study applies the model to the school counseling setting to better understand counselor leadership in context. Using a descriptive survey, data were gathered from 225 school counselors chosen through proportional sampling from secondary schools across Aceh Province. The instrument, developed from Northouse’s leadership skill framework, was adapted to the counseling context through expert validation and psychometric testing. Results from descriptive statistics showed that interpersonal skills were the most prominent among school counselors in Aceh, whereas technical and conceptual skills were less developed. This indicates that counselors excel in relational and communication skills but face challenges in strategic planning, data-driven decision-making, and the management of counseling services. The findings contribute to school counseling leadership research by exposing uneven development across leadership skill dimensions and underscoring the importance of contextualizing leadership models within counseling practice. Practically, the results highlight the need for professional development programs aimed at enhancing technical and conceptual skills, in addition to interpersonal skills. Since this study focused solely on Aceh’s school counselors, the findings should be interpreted within this regional setting and may not fully reflect counselor leadership conditions in other educational environments.